Distribution and virulence of fungal species isolated from yam (Dioscorea spp.) tubers in three agroecological zones of Nigeria - Dania, V.O.; Fadina, O.O.; Ayodele, M.; Kumar, P. Lava (Informa UK Limited, 2020)
Field surveys were conducted in 2012 and 2013 to evaluate the distribution and virulence of fungal isolates associated with tuber rot disease among yam (Dioscorea spp.) producing agroecological zones (AEZs) of Nigeria. A total of 70 and 66 farmers’ fields were surveyed in 2012 and 2013, respectively among three yam species, Dioscorea rotundata, D. alata and D. cayenensis. Fifteen rotted samples were randomly collected per each yam species in fourteen districts across the humid rainforest (HF), the derived savanna (DS) and the southern Guinea savanna (SGS) agroecologies. Twenty-one fungal species were isolated in the HF, 18 species in the DS and 16 in the SGS. The highest rot severity was in HF agroecology in the D. rotundata which varied from 27.2% to 65.7% in 2012 and from 21.1 to 57.4% in 2013, while the SGS agroecology had the least severity. Lasiodiplodia theobromae was the most virulent pathogen with lesion diameter of 26.8–42.1 mm at 14 days after inoculation. Findings provide baseline information for the formulation of management strategies for yam tuber rot disease in Nigeria.